Pengelolaan Sarana Dan Prasarana Di Laboratorium OTKP SMKN 1 Banyudono - Hidyah Ila Agustina; Tutik Susilowati; Tri Murwaningsih (Politeknik Kampar, 2023)
The aim of this research is to determine: (1) the management of facilities and infrastructure in the OTKP laboratory of SMKN 1 Banyudono, (2) the issues encountered regarding the management of facilities and infrastructure in the OTKP laboratory of SMKN 1 Banyudono, (3) the efforts made to optimize the management of facilities and infrastructure in the OTKP laboratory of SMKN 1 Banyudono. This research is a qualitative descriptive approach study. The sampling techniques used are purposive sampling and snowball sampling. Data collection takes the form of observations, interviews and analysis of documents and archives. The data validity test technique uses source triangulation and technical triangulation and member checking of the data that has been obtained is carried out on all informants. The validity of the data is tested using source triangulation and technique triangulation. Data analysis employs interactive analysis. The results of research in the OTKP laboratory of SMKN 1 Banyudono regarding the management of facilities and infrastructure are as follows:1) management includes a) planning, b) procurement, c) storage, d) maintenance, e) supervision, f) disposal, 2) problems encountered include: a) goods held not in accordance with the proposal, b) delay in the distribution of received items, c) limited laboratory space, d) delay in conducting necessary repairs, e) loss of small items, f) there is no laboratory assistant, g) disposal has not been carried out yet, 3) efforts made for optimization include: a) negotiating the development team meeting, b) submitting the next budget, c) the department proactively checking goods that have been held at TU, d) storing in a place that does not interfere with learning, e) routine and incidental maintenance, f) making regulations for borrowing goods, g) proposing the appointment of laboratory assistants, h) disposal has never been carried out.